From Beethoven to Schoenberg: The Micro-Myths of Viennese Classicism and Viennese Modernism in Thomas Mann’s ‘Doktor Faustus’ (Studia theodisca, 2025)
A misreading of Thomas Mann’s Doktor Faustus as a simple allegory lies at the heart of the controversy surrounding Mann’s use of Arnold Schoenberg’s music as a demonically inspired fascist aesthetic. If we look upon Schoenberg’s music as a micro-myth, intersecting and interacting with a counterpart myth, namely Viennese Classicism, then a different picture emerges. This article will take a closer look at the construction and interplay between the micro-myths of Viennese Modernism and Viennese Classicism in Mann’s novel. The article seeks to clarify the use of atonality vs. tonality in the myth-building process and to shed more light on the Mann-Schoenberg controversy.